Time-dependent co-relation of BDNF and CREB mRNAs in adult rat brains following acute psychological stress in the communication box paradigm. (15th June 2016) - Li, Gongying; Wang, Yanmei; Yan, Min; Ma, Hongxia; Gao, Yanjie; Li, Zexuan; Li, Changqi; Tian, Hongjun; Zhuo, Chuanjun
Highlights: No study has investigated BDNF or CREB modulation in rat brains after acute psychological stress. We hypothesize that BDNF and CREB may both be implicated in response to stress in an associated way. The BDNF and CREB pathways are involved in the psychological stress response. The BDNF and CREB pathways may protect the organism from stress-induced aversive processes. Abstract: Psychological stress affects human health, and chronic stress leads to life-threatening diseases, such as depression and post-traumatic stress disorder. Psychological stress coping mechanisms involve the brain-derived neurotrophic factor (BDNF) and downstream cAMP response element binding protein (CREB), which are targets of the adverse effects of stress paradigms. Fourty-seven adult male Sprague-Dawley rats were divided into control, physical stress and six psychological stress groups which were assayed at 0 h, 0.5 h, 1 h, 2 h, 6 h and 24 h after communication box (CB) stress induction. Behavioral assessment using open field and elevated plus maze tests determined that CB stress significantly increased anxiety. After CB stress, the alternation of mRNA levels of BDNF and CREB were assessed at different time points by in situ hybridization. The mRNA levels of BDNF and CREB were significantly decreased, then gradually recovered over 24 h to maximum levels in the hippocampus (CA1 region), prefrontal cortex (PFC), central amygdaloid nuclei (AG), shell of accumbens nucleus (NAC), periaqueductal gray (PAG) and ventral tegmental area, except for the ventral tegmental area (VTA). Moreover, mRNA levels of BDNF and CREB were positively correlated in all examined brain regions, except for the VTA region at 0 and 24 h after CB stress induction. These findings suggest that BDNF and CREB may belong to the same pathway and be involved in psychological stress response mechanisms, and protect the organism from stress induced, aversive processes leading to disease.